Efektivitas Penggunaan Modul Larutan Penyangga Berbasis Inkuiri Terbimbing Terhadap Hasil Belajar Peserta Didik Kelas XI SMA Negeri 13 Padang - Putri, Feby Zania; Iryani, Iryani (Edukimia, 2022)
This studies aims to determine the effectiveness of guides inquiry-based buffer solution modules in achieving learning outcomes of students in class XI MIPA SMA Negeri 13 Padang. The type of this research is pre-experimental with a one-group pretest-posttest design. The subject of this study was the student of XI MIPA 2, which was taken through the purposive sampling techniques. The research instrument was 15 multiple choices question for pretest and posttest, which already tested for validities, reliabilities, index of difficulties of questions, and discriminating index. There was an increase of the average students learning outcome in this study. The data had normal distribution and homogenous variance. The t result showed that tcrit (10.66) score is bigger than ttable (2.73). The N-Gain value was medium, means that the guided in guide inquiry-based buffer solution module is effective to improve students learning outcomes of XI MIPA SMA Negeri 13 Padang students.